Type Classification and Engineering Stability Evaluation of Permafrost Wetlands on the Qinghai–Tibet Plateau - Mao, Xuesong; Zhao, Ying; Wu, Qian; Huang, Wanjun; Han, Liangqing (Frontiers in Earth Science, 2022)
On the Qinghai-Tibet Plateau area, the permafrost and the wetlands are interdependent to form a symbiotic system, which is called permafrost wetlands (PWs). Due to the extremely complex hydrothermal conditions, the PWs have a great impact on road stability. Thus, it is necessary to classify PWs in terms of engineering characteristics and evaluate their engineering stability. In this study, the typical diseases of subgrade in permafrost wetland areas are analyzed based on field investigation. And then, permafrost type, waterlogged area ratio, and meadow development degree are used as the main indicators for the classification of PWs by three-level division method. Finally, a scheme for the engineering stability evaluation of PWs was established based on the fuzzy comprehensive theory, and used for the pre-evaluation of the engineering stability for the proposed Qinghai 224 highway. The results indicate that the longitudinal cracks and uneven deformation are the main road diseases in this area, which are caused by the combined effect of permafrost, waterlogged areas, and meadow development. The PWs are divided into 15 types according to the engineering characteristics. Waterlogged area ratio and meadow development degree are proved to represent the development of underlying permafrost. The influencing factors include climatic environment, permafrost property, and wetland conditions, which have decreased influence on the engineering stability of PWs. The engineering stability of k230+100 and k255+400 is evaluated as basically stable and less stable, and the corresponding measures are adopted. At present, no significant damage occurred on the two road sections. The results suggest that the evaluation model in this paper can be used to pre-evaluate the engineering stability of PWs.